Fundamental Sensor Development in Electrical Resistance Tomography - Ling, En Hong; Ruzairi, Abdul Rahim; Anita, Ahmad; Mohd Amri, Md. Yunus; Khairul, Hamimah Aba; Leow, Pei Ling; Herman, Wahid; Nasarudin, Ahmad; Mohd Fadzli, Abd Shaib; Yasmin, Abdul Wahab; Suzanna, Ridzuan Aw; Mohd Hafiz, Fazalul Rahiman; et al. (Penerbit Universiti Teknologi Malaysia, 2015)
This paper will provide a fundamental understanding of one of the most commonly used tomography, Electrical Resistance Tomography (ERT). Unlike the other tomography systems, ERT displayed conductivity distribution in the Region of Interest (ROI) and commonly associated to Sensitivity Theorem in their image reconstruction. The fundamental construction of ERT includes a sensor array spaced equally around the imaged object periphery, a Data Acquisition (DAQ), image reconstruction and display system. Four ERT data collection strategies that will be discussed are Adjacent Strategy, Opposite Strategy, Diagonal Strategy and Conducting Boundary Strategy. We will also explain briefly on some of the possible Data Acquisition System (DAQ), forward and inverse problems, different arrangements for conducting and non-conducting pipes and factors that influence sensor arrays selections.